(untitled) (Acta Academica: Critical views on society, culture and politics, 2019)
Events that have taken place at several South African universities since 2015 have disclosed many fault lines in the social, political and legal arena. One aspect among many others is the extent to which the idea of the university as a public space has been attacked and all spaces of ‘action and speech’ are under siege. The university as a microcosm of society in general reflects a similar decline of public space, erasure of possibilities for radical dissent and the impossibility of even getting closer to a sense of justice experienced in other spaces. However as the contributions in this edition show it is not only universities and not only South African society that are burdened by neoliberal power.